Effects of Thyroid Function on Hemostasis, Coagulation, and Fibrinolysis: A Mendelian Randomization Study - Ellervik, Christina; Mora, Samia; Kuś, Aleksander; Åsvold, Bjørn; Marouli, Eirini; Deloukas, Panos; Sterenborg, Rosalie B T M; Teumer, Alexander; Burgess, Stephen; Sabater-Lleal, Maria; Huffman, Jennifer; Johnson, Andrew D; et al. (Thyroid (New York, N.Y.), 2021)
Untreated hypothyroidism is associated with acquired von Willebrand syndrome, and hyperthyroidism is associated with increased thrombosis risk. However, the causal effects of thyroid function on hemostasis, coagulation, and fibrinolysis are unknown. In a two-sample Mendelian randomization (MR) study with genome-wide association variants, we assessed causality of genetically predicted hypothyroidism ( = 134,641), normal-range thyrotropin (TSH; = 54,288) and free thyroxine (fT4) ( = 49,269), hyperthyroidism ( = 51,823), and thyroid peroxidase antibody positivity ( = 25,821) on coagulation (activated partial thromboplastin time, von Willebrand factor [VWF], factor VIII [FVIII], prothrombin time, factor VII, fibrinogen) and fibrinolysis (D-dimer, tissue plasminogen activator [TPA], plasminogen activator inhibitor-1) from the CHARGE Hemostasis Consortium ( = 2583-120,246). Inverse-variance-weighted random effects were the main MR analysis followed by sensitivity analyses. Two-sided < 0.05 was nominally significant, and < 0.0011[ = 0.05/(5 exposures × 9 outcomes)] was Bonferroni significant for the main MR analysis. Genetically increased TSH was associated with decreased VWF [β(SE) = -0.020(0.006), = 0.001] and with decreased fibrinogen [β(SE) = -0.008(0.002), = 0.001]. Genetically increased fT4 was associated with increased VWF [β(SE) = 0.028(0.011), = 0.012]. Genetically predicted hyperthyroidism was associated with increased VWF [β(SE) = 0.012(0.004), = 0.006] and increased FVIII [β(SE) = 0.013(0.005), = 0.007]. Genetically predicted hypothyroidism and hyperthyroidism were associated with decreased TPA [β(SE) = -0.009(0.024), = 0.024] and increased TPA [β(SE) = 0.022(0.008), = 0.008], respectively. MR sensitivity analyses showed similar direction but lower precision. Other coagulation and fibrinolytic factors were inconclusive. In the largest genetic studies currently available, genetically increased TSH and fT4 may be associated with decreased and increased synthesis of VWF, respectively. Since Bonferroni correction may be too conservative given the correlation between the analyzed traits, we cannot reject nominal associations of thyroid traits with coagulation or fibrinolytic factors.